Ğevondi patmut’yun - 880-01 Ghewond, Yerets, 8. yy. (Los Angeles)
xii, 245 sayfa
Keywords: “Ghewond is considered a trustworthy historian. He correctly lists the caliphs and the lengths of their reigns, except for the reigns of the initial three caliphs. He correctly lists the names and reigns of the ostikans or Muslim governors of the newly-created administrative unit called Arminiya, which included Armenia, East Iberia (Georgia), and parts of Aghuania. He was a supporter of the ambitions of the Bagratid family and, according to the colophon at the end of his History, wrote under the patronage of Shapuh Bagratuni, son of Smbat sparapet (commander-in-chief), whose activities are recorded in the work“ --